2020
DOI: 10.1016/j.cegh.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Crucial predicting factors of under-five mortality in Sierra Leone

Abstract: includes in countries which exhibit the highest prevalence of under-five mortality in the world. A range of factors are known to have challenged the under-five survival in the country; some comprise outbreak of epidemics, socioeconomic inequalities, regional disparities, and unsuccessful implementation of healthcare initiatives. The present study aims to identify crucial predictors of under-five survival. Methods: This paper used the Sierra Leone Demographic and Health Survey (SLDH, 2013). A Cox Proportional H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
(31 reference statements)
4
10
1
Order By: Relevance
“…The result is consistent with previous research findings which highlighted the negative association of maternal education with childhood mortality in developing countries. [5][6][7][8]42 Our research findings offer support to "Chicago-Columbia hypothesis" which states that female education increases female efficiency in the production of child health. 43 In this study, age of mother at the first delivery was found to be associated with a considerable risk of the survival of under-five children.…”
Section: Discussionsupporting
confidence: 70%
“…The result is consistent with previous research findings which highlighted the negative association of maternal education with childhood mortality in developing countries. [5][6][7][8]42 Our research findings offer support to "Chicago-Columbia hypothesis" which states that female education increases female efficiency in the production of child health. 43 In this study, age of mother at the first delivery was found to be associated with a considerable risk of the survival of under-five children.…”
Section: Discussionsupporting
confidence: 70%
“…Out of 22 studies, 18 studies were conducted in 11 countries in the Africa region (Burkina Faso [ 19 21 ]: 3, Ethiopia [ 22 24 ]: 3, Nigeria [ 25 – 27 ]: 3, Ghana [ 28 , 29 ]: 2, Lesotho [ 30 ]: 1, sub-Saharan (combine study of five-country; Chad, Democratic Republic (DR) of Congo, Mali, Niger, and Zimbabwe) [ 31 ]: 1, Zambia [ 32 ]: 1, Kenya [ 33 ]: 1, DR Congo [ 34 ]: 1, Sierra Leone [ 35 ]: 1, and Tanzania [ 36 ]: 1). One study included was conducted in Nepal [ 37 ] and another one in Bangladesh [ 38 ] from South-East Asian region.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 shows factors identified by two or more studies conducted in African countries. Among 18 articles, 9 (50%) articles [ 20 , 24 26 , 29 , 31 , 32 , 35 , 36 ] found that the size of child at birth is a major determinant playing an important role in under-five mortality. Age of mother, place of residence, sex of child, and mother's education are other important variables explored by 7 (38.9%) studies conducted in these countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for under-five mortality are due to many factors, from the community level and socio-economic factors to the individual level (Ogbo et al, 2019;Yaya et al, 2020). Previous research showed that the community level, such as the area of residence, was the most common predictor of under-five mortality (Naz et al, 2020), as geographical areas have different characteristics for health and environmental factors (Chowdhury et al, 2020;Yaya et al, 2020). Several studies in developing countries have shown that maternal socioeconomic characteristics are a strong phenomenon in determining the risk of child mortality (Fikru et al, 2019;Nisar & Dibley, 2014).…”
Section: Introductionmentioning
confidence: 99%